Ciphers and Executioners: How 3′-Untranslated Regions Determine the Fate of Messenger RNAs - Mayya, Vinay K.; Duchaine, Thomas F. (Frontiers in Genetics, 2019)
The sequences and structures of 3’-untranslated regions (3’UTRs) of messenger RNAs govern their stability, localization, and expression. 3’UTRs regulatory elements are recognized by a diverse variety of trans-acting factors that include microRNAs (miRNAs) and their associated machinery, and RNA-binding proteins (RBPs). In turn, these factors instigate common mechanistic strategies to execute the regulatory programs encoded by 3’UTRs. Here, we review classes of factor that recognize 3’UTR regulatory elements and the effector machineries they guide towards mRNAs to dictate their expression and fate. We outline illustrative examples of competitive, cooperative, and coordinated interplay such as mRNA localization and localized translation. We further review the recent advances in mRNP granules and phase transition, and their significance for the functions of 3’UTRs. Finally, we highlight some of the most recent strategies aimed at deciphering the complexity of the regulatory codes of 3’UTRs, and identify some of the important remaining challenges.